Productivity enhancement in sugarcane through new variety Co 0212 - Saravanakumar, S (Indian Farming, 2021)
Sugarcane is the main source of sucrose being cultivated over 200,000 ha in Tamil Nadu and 10% area cultivated in Erode district. The average productivity of sugarcane in Erode district is 104 t/ ha, which is low when compared to its potential yield. To improve the productivity of sugarcane KVK conducted on Farm trial on assessing the performance of the Co 0212 variety for wider adoption in the district. The variety Co 0212 recorded 17.24% more yield than the existing variety Co 86032. Success of the technology was demonstrated in association with ICAR-Sugarcane Breeding Institute and sugar mills for wider adoption in Erode district.